MAXILLARY INCISOR TRAUMA IN PATIENTS WITH CLASS II DIVISION 1 DENTAL MALOCCLUSION: ASSOCIATED FACTORS - Elif Yaman DOSDOĞRU; Feyza Nur GÖRKEN; Arzu Pınar ERDEM; Evren ÖZTAŞ; Gülnaz MARŞAN; Elif SEPET; Zeynep AYTEPE (Istanbul University, 2017)
Purpose: The aim of this study was to assess the association between the presence of maxillary incisor trauma (MIT) with age, gender, dentition type, the degree of overjet (OJ), lip form, respiratory type and dental arch form in patients with Class II division 1 dental malocclusion. Subjects and Methods: 256 patients (mean age: 15.80 ± 2.2) were included in this study. The patients' gender, dentition type, superior lip form, dental arch form and respiratory type were recorded. Participants were divided into four groups according to the severity of OJ: 3.5 mm <Group 1 (OJ I) ≤6 mm with competent lip, 3.5 mm<Group 2 (OJ II) ≤ 6 mm with incompetent lip, 6 mm<Group 3 (OJ III) ≤9mm, 9 mm<Group 4 (OJ IV). Mann Whitney-U test was used to examine the group differences for trauma and non-trauma groups. Logistic regression analysis was used to assess the factors for trauma and their risk indicators. Results: 3.5 mm< OJ II≤ 6 mm with incompetent lip had the highest odds of experiencing MIT among the OJ groups with an odds ratio (OR) of 3.143 and 95% confidence interval (CI) 1.125-2.779. The odds were 3.572 times higher in the group with short lip form than found in the group with normal lip form (OR 3.572, 95% CI 1.130-2.340). Conclusion: The age, gender, respiratory type and dental arch form were not significantly associated the risk of MIT. OJ between 3.5 mm and 6 mm (with incompetent lip) and short lips increased the risk of having maxillary incisor trauma in patients with Class II division 1 malocclusion.